Association between different levels of dysglycemia and metabolic syndrome in pregnancy - Negrato, Carlos A. [UNESP]; Jovanovic, Lois; Rafacho, Alex [UNESP]; Tambascia, Marcos A.; Geloneze, Bruno; Dias, Adriano [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Biomed Central Ltd., 2009)
Background: In this study, we sought to evaluate the prevalence of metabolic syndrome (MS) in a cohort of pregnant women with a wide range of glucose tolerance, prepregnancy risk factors for MS during pregnancy, and the effects of MS in the outcomes in the mother and in the newborn.Methods: One hundred and thirty six women with positive screening for gestational diabetes mellitus (GDM) were classified by two diagnostic methods: glycemic profile and 100 g OGTT as normoglycemic, mild gestational hyperglycemic, GDM, and overt GDM. Markers of MS were measured between 2428(th) during the screening.Results: The prevalence of MS was: 0%; 20.0%; 23.5% and 36.4% in normoglycemic, mild hyperglycemic, GDM, and overt GDM groups, respectively. Previous history of GDM with or without insulin use, BMI >= 25, hypertension, family history of diabetes in first degree relatives, non-Caucasian ethnicity, history of prematurity and polihydramnios were statistically significant prepregnancy predictors for MS in the index pregnancy, that by its turn increased the adverse outcomes in the mother and in the newborn.Conclusion: The prevalence of MS increases with the worsening of glucose tolerance; impaired glycemic profile identifies pregnancies with important metabolic abnormalities even in the presence of a normal OGTT, in patients that are not classified as having GDM.